Pengembangan Media Mobile Learning Menggunakan Program Appy Pie Untuk Meningkatkan Hasil Belajar Mahasiswa - Muhammad Naharuddin Arsyad; Dinna Eka Graha Lestari (Proceedings of The ICECRS, 2019)
The industrial revolution 4.0 is a trend in the industrial world that combines data exchange and automation technology. This trend changes human life in various fields including education. The use of this technology in education is still minimal , even though the instruments to implement it already exist. For example smartphone technology. Users of Android smartphones among students are very numerous. Therefore, the author took the initiative to develop and design an Android-based mobile learning media so that it was interesting by using an online builder program called "Appy Pie". The use of mobile learning media can make it easier for students to obtain educational and interesting information. Therefore, the learning process can be in accordance with the purpose of improving student learning test of IKIP Budi Utomo Malang. The method in this study is Research and Development with the DDD-E model. The results of validity by instructional media experts are 85% (very valid) and the results of validation by material experts are 90% ( very valid ). For the learning result obtained the average value of post-test is greater than the average value of pre-test (81,33 > 69,33). In generally, students experience an increase in learning test after using mobile learning media in the material history of the European industrial revolution in European history courses.